An appraisal of the genus Ptiloneura Enderlein (Insecta: Psocodea: Psocomorpha: Ptiloneuridae), new species from Colombia and Peru, and a key to the males - Obando, Ranulfo González; Gironza, Nancy Carrejo; Panche, Jeferson; Aldrete, Alfonso Neri García (Zootaxa, 2020)
We describe and illustrate 15 species of Ptiloneura, from Colombia and Peru. The number of species of Ptiloneura is raised to 34, of which 28 (82.3%) are Colombian. One species is from Brazil, four species are from Peru, one is from Nicaragua and two species are from Venezuela. Two species are shared between Colombia and Peru, one species is shared between Colombia and Venezuela, and 25 species are endemic to Colombia. An identification key to the males and a phylogenetic analysis of Ptiloneura are included.